HOW DO ASPERITIES FRACTURE? AN EXPERIMENTAL STUDY OF UNBROKEN ASPERITIES - Lei X. (My University, 2003)
The fracture of a shear fault containing several unbroken asperities in a granitic porphyry is examined in detail via acoustic emission (AE) data collected by a high-speed multi-channel waveform recording system. The experimental results reveal that a quasi-static nucleation of the shear faulting corresponds to the fracture of coupled asperities on the fault plan. AEs caused by the fracture of individual asperities exhibit similar characteristics to the sequence for natural earthquakes, including foreshock, mainshock, and aftershock events. Foreshocks, initiated at the edge of the asperity, occur with an event rate that increases according to a power law of the temporal distance to the mainshock, and with a decreasing b-value (from ∼1.1 to ∼0.5). One or a few mainshocks then initiate at the edge of the asperity or the front of the foreshocks. The aftershock period is characterized by a remarkable increase and subsequent gradual decrease in b-value and a decreasing event rate obeying the modified Omori law, which has been well established for earthquakes. The fracture of neighboring asperities is then initiated after the mainshock of a particular asperity, presumably due to redistribution of the strain energy accumulated within an asperity, which is released by the mainshock, resulting in enhancement of the stress concentration around the nearest neighboring intact asperities. The progressive fracturing of multiple, coupled asperities during the nucleation of shear faulting results in short-term precursory fluctuations in both b-value and event rate, which may prove useful information in the prediction of failure of the main fault plane of seismic earthquakes.